Examining Interdisciplinary Research Collaborations to Inform Agricultural and Environmental Science Communication: A Meta-synthesis Approach - Kristin E Gibson; Allison R Fortner; Alexa J Lamm; Madison C. Wilson; Allen J Moore (Journal of Applied Communications, 2021)
Agriculturalists and environmentalists must navigate complex challenges as the global population continues to increase and environmental resources are depleted. Colleges of agricultural and environmental sciences are tasked with addressing the nexus between environmental and agricultural challenges through research, education, and communication. However, the amount of research being conducted with both agriculture and the environment considered is largely unknown and, as a result, their corresponding communication messages may not provide coherent messages from the college. Therefore, the purpose of this study was to identify if research within a college of agricultural and environmental sciences takes a holistic approach so that communication efforts coming from the college can encompass both perspectives. The data were collected from a web-based system containing university research publications and analyzed using a thematic analysis and meta-synthesis. The meta-synthesis revealed 212 codes overlapping agricultural and environmental themes compared to the total 4,325 codes found across all publications. The findings indicated there was a limited amount of collaboration occurring between environmental and agricultural researchers within the college. Without collaborative research, agricultural communicators cannot develop science communication efforts that holistically integrate evidence-based science. As new challenges emerge at the nexus of agriculture and the environment, researchers must shift toward a collaborative and interdisciplinary approach to ensure the science communication efforts sharing their findings are inclusive.
Keywords: agricultural and environmental science research; science communication; colleges of agricultural and environmental sciences; meta-synthesis; thematic analysis